1948
DOI: 10.1021/ie50459a004
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Process For Production of 2,2-Dinitropropane

Abstract: 381general unit operations equipment such as filter presses, pumps, and centrifugals, which can be adapted to almost any unit process. Here the fundamental chemical changes are initially applied and the equipment is checked for proper design and adaptability to the economic factors of a specific industry.To stimulate further research and also to enable practicing chemical engineers to make better use of the present state of knowledge, INDUSTRIAL AND ENG~NEERINQ CHEMISTRY is now organizing a yearly review of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…121 Already during World War II, nitration was conducted in a continuous flow reactor. 122,123 Continuous systems were developed and patented for the synthesis of explosive materials such as nitroglycerine, ethylene glycol dinitrate, diethylene glycol dinitrate, cyclotrimethylenetrinitramine and pentaerythritol tetranitrate. 122 The experimental setup for continuous flow nitrations covered in literature typically exists of two feeds, containing the substrate and the nitrating agents, a micromixing device in a thermal bath at a constant temperature and a controlled residence time.…”
Section: Nitrationmentioning
confidence: 99%
“…121 Already during World War II, nitration was conducted in a continuous flow reactor. 122,123 Continuous systems were developed and patented for the synthesis of explosive materials such as nitroglycerine, ethylene glycol dinitrate, diethylene glycol dinitrate, cyclotrimethylenetrinitramine and pentaerythritol tetranitrate. 122 The experimental setup for continuous flow nitrations covered in literature typically exists of two feeds, containing the substrate and the nitrating agents, a micromixing device in a thermal bath at a constant temperature and a controlled residence time.…”
Section: Nitrationmentioning
confidence: 99%
“…3.1.3 Vapour phase nitration. In an early study on the continuous flow nitration of 2-nitropropane ( 52 ), Denton et al [ 22 ] demonstrated that high pressure and high temperature conditions, i.e., 900 to 1200 psi and 203–232 °C, using an equimolar nitric acid (70%) gives about 50% yields per pass ( Scheme 15 ). Their reaction assembly consists of a stainless steel preheater tube (outer diameter of 6.24 mm) passed through a 40 inch long 20 mm outer diameter.…”
Section: Reviewmentioning
confidence: 99%